2022
DOI: 10.1039/d2cc04544c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient blue TADF-type organic afterglow materialviaboric acid-assisted confinement

Abstract: A heat treatment method is developed to produce blue afterglow materials, achieving a photoluminescence quantum yield of 65% and an emission lifetime of 0.18 s (afterglow: >2 s). The afterglow...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…High-resolution C 1s spectra presented three peaks at 288.8, 286.9, and 284.8 eV, corresponding to O–CO, C–O, and sp 2 C (Figure d) . The high-resolution B 1s spectrum was fitted into three peaks at 193.4, 194.2, and 195.5 eV, corresponding to –BCO 2, B 2 O 3 , and B–O bonds (Figure e). ,, This is consistent with the results of XRD and FTIR, which indicated that a partial amount of BA transferred into B 2 O 3 , and boron atoms are surrounded by carbon and oxygen atoms. Figure f shows the UV–vis absorption spectra of heated BA, Nap-BOH, and samples.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…High-resolution C 1s spectra presented three peaks at 288.8, 286.9, and 284.8 eV, corresponding to O–CO, C–O, and sp 2 C (Figure d) . The high-resolution B 1s spectrum was fitted into three peaks at 193.4, 194.2, and 195.5 eV, corresponding to –BCO 2, B 2 O 3 , and B–O bonds (Figure e). ,, This is consistent with the results of XRD and FTIR, which indicated that a partial amount of BA transferred into B 2 O 3 , and boron atoms are surrounded by carbon and oxygen atoms. Figure f shows the UV–vis absorption spectra of heated BA, Nap-BOH, and samples.…”
Section: Resultssupporting
confidence: 85%
“…4, 194.2, and 195.5 eV, corresponding to −BCO 2, B 2 O 3 , and B−O bonds (Figure 4e). 36,38,39 This is consistent with the results of XRD and FTIR, which indicated that a partial amount of BA transferred into B 2 O 3 , and boron atoms are surrounded by carbon and oxygen atoms. Figure 4f shows the UV−vis absorption spectra of heated BA, Nap-BOH, and samples.…”
Section: Resultssupporting
confidence: 85%
“…The epoxy composites were produced by adding fine powder of boric acid (H 3 BO 3 , Chempur Company, Piekary Śl ąskie, Poland) to the resin. This compound has a wide range of applications [31,36,[52][53][54], one of which is to improve the flame retardancy of polymers [31,39]. The ortho form of boric acid was used, as shown in Figure 1c [52].…”
Section: Boron Acid/epoxy Resin Compositesmentioning
confidence: 99%